Subcritical Water-supercritical CO2 (SCW-SCCO2) Hydrothermal Liquefaction (HTL) of Oil Palm Derived Lignin via Low-Transition-Temperature Mixtures (LTTMs) into Bio-oil - Elatta, Odita (University of Malaysia, Sarawak, 2025)
Our current environmental challenges demand long-term prospective efforts for sustainable development to be solved. The pursuit of green energy has designed more environmentally friendly designer solvents are produced known as Deep Eutectic Solvents (DES) and later dubbed Low Transition Temperature Mixtures (LTTMs). Empty Fruit Bunch (EFB) from the oil palm industry was delignified using LTTMs to extract lignin and later undergo subcritical water-supercritical CO2 (SCW-SCCO2) hydrothermal liquefaction (HTL) to produce bio-oil. The hydrogen bonding in choline chloride (ChCl)-malic acid LTTMs have been determined through FT-IR analysis. This system's delignification of EFB removed a considerable 31.98% of lignin in just 4 hours and the LTTMs showed a recoverability ≥90% (1st recovery = 93.8% & 2nd recovery = 91.1%). SCW-SCCO2 HTL was investigated in this research, and ideal conditions were found at 275°C, 25 MPa, with a 1:3 lignin-to-water ratio. Phenolic compounds were identified using GC-MS analysis as the primary target compounds in bio-oil analysis, suggesting a route from EFB to lignin, derivatives, and eventually phenolics. Based on the kinetic studies, the rate constant increased from 9.59x10-4 to 1.06x10-3s-1 with temperatures between 250-300°C. A temperature-dependant kinetic model was demonstrated using the Arrhenius equation, which estimated the activation energy (E) to be 4.2 kJ/mol and the pre-exponential factor (A) to be 2.13 x10-3 s-1. An empirical kinetic model (modified Reverchon-Sesti Osseo) was used in predicting the bio-oil yield with an outcome of R2 for 250°C (0.87), 275°C (0.104) and 300°C (0.843).